Comparison of outcomes between anticoagulation and antiplatelet therapies for intracranial arterial dissections - Lee, Seong-Joon; Kim, Min; Park, So Young; Park, Ji Hyun; Park, Bumhee; Jung, Woo Sang; Choi, Jin Wook; Lim, Yong Cheol; Hong, Ji Man; Lee, Jin Soo (Frontiers in Neurology, 2024)
BackgroundThis study aimed to evaluate real-world data on the differences in outcomes between antiplatelet (AP) and anticoagulation (AC) therapies for intracranial arterial dissection (IAD).MethodsThis study included patients with symptomatic unruptured IAD between 2010 and 2021 that were treated with anti-thrombotics. Patients were dichotomized to AC and AP based on a treatment policy analysis. Primary endpoints were a composite of ischemic early neurological deterioration, recurrent ischemic or hemorrhagic stroke, or 3-month mortality. Arterial changes were evaluated both in the early (during admission) and late (after discharge) periods. A treatment effectiveness analysis was also performed with AC, AP and a third group of antithrombotic cross-overs. Propensity score matching (PSM) was used to adjust significant baseline differences.ResultsIn unruptured IAD patients (N = 311), the AC group (N = 211) presented with a higher rate of ischemic stroke or TIA (74.4% vs. 51.0%, p < 0.001) and steno-occlusive morphology (vs. dilatation, 63.0% vs. 39.0%, p < 0.001) compared to AP group (N = 100). After PSM, there was no difference in rates of primary endpoint (9.4% vs. 6.5%, p = 0.470). The results of the treatment effectiveness analysis resembled that of the treatment policy analysis. However, there was a high rate of cross-overs from AC to AP (57/211 [27.0%]). In this group, there was a higher rate of early arterial changes (26.8% vs. 13.1%, p = 0.019) compared to the AC group.ConclusionIn patients with unruptured IAD, this study did not show differences in primary endpoints according to antithrombotic regimen, while there was a high rate of cross-overs from AC to AP.